Dialogical and Mediatory Potential of an Integral Ecology - Jaromi, Stanisław (Studia Ecologiae et Bioethicae, 2020)
The encyclical Laudato si’ is a Catholic document synthesizing the reflection on the main issues related to ecology as well as to nature and climate protection. It provides a new perspective for ecological activity in the light of integral ecology principles. In many countries, this encyclical has become a point of reference for Catholics in the context of the ecological crisis, especially by the fact of its highlighting the religious and spiritual perspective and giving concrete examples of both ecological and Christian lifestyles. Chapter 5 of the encyclical outlines, moreover, the concept of dialogue that brings hope for abandoning the spiral of self-destruction in which humanity is now sinking. The concept of communicative humanism and its mechanisms i.e. actions restoring values and creating a community have been proposed to establish the platform for this dialogue. The program is based on personalism and Christian hermeneutics, and its goal is a Church interested in the world and its problems, a one which on a par with others wants to say STOP to the destruction of the earth and its irresponsible exploitation.